Integrated Autofluorescence Characterization of a Modified-Diet Liver Model with Accumulation of Lipids and Oxidative Stress. (9th June 2014) - Croce, Anna Cleta; Ferrigno, Andrea; Piccolini, Valeria Maria; Tarantola, Eleonora; Boncompagni, Eleonora; Bertone, Vittorio; Milanesi, Gloria; Freitas, Isabel; Vairetti, Mariapia; Bottiroli, Giovanni
Abstract : Oxidative stress in fatty livers is mainly generated by impaired mitochondrial β -oxidation, inducing tissue damages and disease progression. Under suitable excitation, light liver endogenous fluorophores can give rise to autofluorescence (AF) emission, the properties of which depend on the organ morphofunctional state. In this work, we characterized the AF properties of a rat liver model of lipid accumulation and oxidative stress, induced by a 1–9-week hypercaloric methionine-choline deficient (MCD) diet administration. The AF analysis (excitation at 366 nm) was performed in vivo, via fiber optic probe, or ex vivo . The contribution of endogenous fluorophores involved in redox reactions and in tissue organization was estimated through spectral curve fitting analysis, and AF results were validated by means of different histochemical and biochemical assays (lipids, collagen, vitamin A, ROS, peroxidised proteins, and lipid peroxidation -TBARS-, GSH, and ATP). In comparison with the control, AF spectra changes found already at 1 week of MCD diet reflect alterations both in tissue composition and organization (proteins, lipopigments, and vitamin A) and in oxidoreductive pathway engagement (NAD(P)H, flavins), with a subsequent attempt to recover redox homeostasis. These data confirm the AF analysis potential to provide a comprehensive diagnostic information on negative effects of oxidative metabolism alteration.